Interpretasi Makna Hidayah Dalam al-Quran (Telaah Pemikiran Al-RÄgib al-Aá¹£fahÄnÄ«) - Wali Ramadhani (UIN Siber Syekh Nurjati Cirebon, 2022)
This article explains the meaning of hidayah in the Qurâ€™an from the perspective of al-RÄgib al-Aá¹£fahÄnÄ«. Verses about hidayah are presented in the Qur'an in various ways. In some places, they seem contradictory. Through of descriptive-analytical, the author tries to explain about hidayah in the Qurâ€™an from al-RÄgib's presentation recorded in his magnum-opus MufradÄt alfaáº“ al-QurÄn. He was one of the commentators in the 5th century H. The verses about hidayah described in the Qurâ€™an are classified by al-RÄgib into four stages; the first stage is hidayah obtained by all living things on this earth (garizah, natural nature and thinking power), the second stage is hidayah given to humans in the form of preaching from the prophets and apostles, the third stage is hidayah given special by Allah to those who ask and want guidance (taufiq), the fourth stage is hidayah obtained by humans in the hereafter, namely the guidance of Allah in the beauty and pleasures of heaven.